Photoluminescence and unique magnetoluminescence of transparent (Tb1-xYx)3Al5O12 ceramics. Issue 7 (May 2020) - Xing, Zhifeng; Lun, Mengmeng; Wu, Wanying; Song, Hanzhao; Yao, Aihua; Zhou, Xunsheng; Wang, Yinzhen; Chu, Benli; Li, Wei; He, Qinyu; He, Guannan
Abstract: Luminescent transparent ceramics (Tb1-x Yx )3 Al5 O12 (x = 0, 0.2, 0.5, 0.8) are successfully prepared by a solid-state method with additional hot isostatic pressing (HIP) treatment, and the structure and properties are investigated by XRD, SEM, PL, UV–Vis spectrophotometry and ellipsometry. The Y-containing samples are shown to be solid solution phases between TAG and YAG. The PL intensity is 14 times stronger with the incorporation of 80 mol.% Y, and the 5 D4 → 7 F5 emission lifetime of Tb 3+ is prolonged from 0.357 to 3.035 ms at room temperature. A unique magnetoluminescence emerges upon the incorporation of Y, showing an interesting emission decrease to 55% as the Y content reaches 80 mol.%. Remarkably, this magnetoluminesence can occur at room temperature without an intense magnetic field. Based on our work, transparent (Tb1-x Yx )3 Al5 O12 ceramics exhibit the potential for applications in green emitters, optical instruments and photoelectric devices. In particular, the magnetoluminescence provides a simple, noncontact and nondestructive route for probing magnetic fields.